Impacts of Climatic Factors on Vegetation Species Diversity, Herbaceous Biomass in Borana, Southern Ethiopiaq - Asfaw EJO; Tessema Zewedu; Ibsa Aliyi Usmane (Global Journal of Ecology - Peertechz Publications, 2020)
The study was conducted in three districts of Borana Zone, with the objective to determining the impacts of climatic factors on vegetation species diversity, herbaceous biomass yield of Borana rangelands under commonial grazing rangeland types during end of growing season. The most types rangeland of communial properties are traditional enclosure and continuous grazing rangeland from in where our different data were collected. Within both rangeland types of each districts 20 m × 20 m plots that placed at 200 m distances intervals with three replication was used to collect woody vegetation. The data of herbaceous plant community was collected from seventeen quadrants (1 m ×1 m) that layout in the main plot. The collected data was analyzed by linear regression to determine the impact of climate factors. The herbaceous species richness, diversity and biomass study sites had highly significantly difference (P < 0.001) and positive linear with mean annual precipitation. There is significantly difference (P < 0.05) and negative linear in woody species richness and diversity. Both herbaceous and woody plant species richness and diversity of study areas had a negative linear with mean annual temperature. Climate factors specieally rianfall have a great impact on semi-arid rangeland ecosystems of study areas. Therefore, semi-arid rangeland user should be considering climatic factors to improve productivity of rangeland at semi-arid enviroments.